Twin Screw Melt Granulation of Simvastatin: Drug Solubility and Dissolution Rate Enhancement Using Polymer Blends - Rasha M. Elkanayati; Indrajeet Karnik; Prateek Uttreja; Nagarjuna Narala; Sateesh Kumar Vemula; Krizia Karry; Michael A. Repka (Pharmaceutics)
Background/Objectives: This study evaluates the efficacy of twin screw melt granulation (TSMG), and hot-melt extrusion (HME) techniques in enhancing the solubility and dissolution of simvastatin (SIM), a poorly water-soluble drug with low bioavailability. Additionally, the study explores the impact of binary polymer blends on the drug’s miscibility, solubility, and in vitro release profile. Methods: SIM was processed with various polymeric combinations at a 30% w/w drug load, and a 1:1 ratio of binary polymer blends, including Soluplus® (SOP), Kollidon® K12 (K12), Kollidon® VA64 (KVA), and Kollicoat® IR (KIR). The solid dispersions were characterized using modulated differential scanning calorimetry (M-DSC), powder X-ray diffraction (PXRD), and Fourier-transform infrared spectroscopy (FTIR). Dissolution studies compared the developed formulations against a marketed product. Results: The SIM-SOP/KIR blend showed the highest solubility (34 µg/mL), achieving an approximately 5.5-fold enhancement over the pure drug. Dissolution studies showed that SIM-SOP/KIR formulations had significantly higher release profiles than the physical mixture (PM) and pure drug (p < 0.01). Additionally, their release was similar to a marketed formulation, with 100% drug release within 30 min. In contrast, the SIM-K12/KIR formulation exhibited strong miscibility, but limited solubility and slower release rates, suggesting that high miscibility does not necessarily correlate with improved solubility. Conclusions: This study demonstrates the effectiveness of TSMG, and HME as effective continuous manufacturing technologies for improving the therapeutic efficacy of poorly water-soluble drugs. It also emphasizes the complexity of polymer–drug interactions and the necessity of carefully selecting compatible polymers to optimize the quality and performance of pharmaceutical formulations.